Sociological Analysis of Gender Relations in the “Uzbekistan–2030” Strategy - Malika Mardieva (Scientific Trends, 2025)
The “Uzbekistan–2030” Strategy represents a comprehensive framework for national development, with gender equality recognized as a key driver of social, economic, and political progress. This paper provides a sociological analysis of gender relations in Uzbekistan within the Strategy, examining historical-cultural norms, institutional structures, women’s economic and educational participation, gender-based violence, and family roles. Using qualitative methods and secondary data analysis, the study identifies barriers to equality and highlights the Strategy’s potential to transform gender relations through legal reforms, educational policies, economic empowerment, and sociocultural interventions. While significant progress has been made, challenges remain in changing cultural norms, rural-urban disparities, and structural inequalities.
Keywords: Gender relations; Uzbekistan–2030; gender equality; sociological analysis; women’s empowerment; social reform; patriarchy; education; political participation; Central Asia